2018
DOI: 10.1007/s00464-018-6530-4
|View full text |Cite
|
Sign up to set email alerts
|

Transanal total mesorectal excision (TaTME) versus laparoscopic TME for MRI-defined low rectal cancer: a propensity score-matched analysis of oncological outcomes

Abstract: Background While a shift to minimally invasive techniques in rectal cancer surgery has occurred, non-inferiority of laparoscopy in terms of oncological outcomes has not been definitely demonstrated. Transanal total mesorectal excision (TaTME) has been pioneered to potentially overcome difficulties experienced when operating with a pure abdominal approach deep down in the pelvis. This study aimed to compare short-term oncological results of TaTME versus laparoscopic TME (lapTME), based on a strict … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
78
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(81 citation statements)
references
References 42 publications
2
78
1
Order By: Relevance
“…In the international literature, a wide range of categories are used for rectal cancer volume at hospital level. Van Gijn et al calculated median cut-off points from published rectal cancer hospital volume studies, leading to a definition of a high-volume hospital a performing more than 24 (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) rectal cancer resections per year and low-volume hospitals performing 9 (6-14) [28]. This hampers interpretation of the available literature on this topic.…”
Section: Discussionmentioning
confidence: 99%
“…In the international literature, a wide range of categories are used for rectal cancer volume at hospital level. Van Gijn et al calculated median cut-off points from published rectal cancer hospital volume studies, leading to a definition of a high-volume hospital a performing more than 24 (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) rectal cancer resections per year and low-volume hospitals performing 9 (6-14) [28]. This hampers interpretation of the available literature on this topic.…”
Section: Discussionmentioning
confidence: 99%
“…One thousand two hundred and forty-seven citations were retrieved from the search strategy. Finally, twelve studies [24][25][26][27][28][29][30][31][32][33][34][35] were included in the analysis, with a total of 899 patients (411 patients in TaTME group, 488 patients in LaTME group) ( Figure 1). The characteristics of eligible studies are shown in Table I.…”
Section: Resultsmentioning
confidence: 99%
“…There were six studies [24-27, 31, 34] that reported CRM, eleven studies [24][25][26][28][29][30][31][32][33][34][35] that reported positive CRM, eight studies [24-27, 30, 32-34] that reported DRM and five studies [25,28,31,34,35] that reported positive DRM. No differences were found in these pathological outcomes ( Figure 5).…”
mentioning
confidence: 99%
“…Several studies reported that Ta-TME achieved similar technical success and perioperative outcomes than laparoscopic TME, with a lower conversion rate [90] . Recent studies also showed that serious complications secondary to wrong down-to-up dissection planes were not despicable, same for anastomotic leaks [91] . To improve the accuracy of the transanal dissection, robotic technology could also be helpful [92] .…”
Section: Robotic-assisted Transanal Tmementioning
confidence: 99%